CHARACTERIZATION OF CYSTIC PANCREATIC LESIONS ON EUS, A SINGLE CENTRE EXPERIENCE - Khan, Faryal Riaz Khan; Rao Saad Ali Khan; Ehtesham Haider; Fuad Ahmad Siddiqi; Muhammad Mehdi Naqvi; Salahuddin; Zara Riaz Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Pancreatic cystic lesions are increasingly diagnosed these days due to better imaging techniques. It is important to detect the lesions and perform a detailed analysis as some of them are potentially malignant. Methods: From April 2023 to September 2023, all patients with recurrent and/ or persistent abdominal pain lasting for more than a week were assessed in the gastroenterology department of Pak-Emirates military hospital, Rawalpindi. Detailed history and examination was done. Relevant laboratory tests and an ultrasound abdomen were also carried out. Those with pancreatic lesions on ultrasound abdomen underwent EUS (endoscopic ultrasound). Amongst those undergoing EUS, 88 patients were found to have cystic pancreatic lesions. These 88 patients underwent detailed assessment with EUS-FNA (endoscopic ultrasound - fine needle aspiration) so that these pancreatic cysts could be characterized. Only some of the patients undergoing EUS-FNA had one or more of the worrisome features (solid component within the cyst, main pancreatic duct & gt; 5 mm in size, symptoms related to the cyst, family history of pancreatic cancer), and later underwent surgical resection. EUS was done with the patient in the left lateral decubitus position under intravenous sedation with midazolam. During the procedure, the patient was monitored using the cardiac monitor. Images of the pancreas, gallbladder and bile tree were obtained with the echoendoscope in the stomach and duodenum. Informed consent for the study and the endoscopic procedure was obtained from all patients. The study protocol was approved by the hospital ethics committee. Results: The study population included 50 females and 38 males. Many of these patients had one or more episodes of pancreatitis in the recent past. Most cystic lesions were found in the pancreatic body. The largest number of lesions were due to pancreatic pseudocysts. EUS was performed successfully in all patients. Findings have been summarised in the table according to gender. Conclusion: Identifying pancreatic cystic neoplasms is important since some have malignant potential. In that regard, EUS-FNA is a useful diagnostic modality and it can influence the management plan.